Leadership and technology innovation: Practices in Cotabato city division - Lipura, Ma. Rosalie F. (Edelweiss Applied Science and Technology, 2025)
Digital literacy is a fundamental technical skill integrated into the K-12 curriculum through an intensified ICT (Information and Communications Technology) program. To support schools with both online and offline instructional resources, various sectors have initiated programs to adapt to technological changes. The sustainability of policies involving ICT innovation in schools is influenced by adherence to effective leadership practices. Although public schools provide programs with ICT resources, technological advancement remains a significant educational challenge affecting sustainability, including initiatives, practices, and their association with leadership. Consequently, the researcher aims to examine leadership practices in public elementary schools within the Cotabato City Division that have implemented and sustained technological innovations. A descriptive correlational research design was employed, utilizing survey questionnaires for data collection. Total enumeration was used to determine the sample size. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS). The study found that elementary school heads and ICT coordinators demonstrate a satisfactory level of ICT leadership and innovation. Areas such as community partnerships, mentoring, technical support, and training for teachers and pupils require ongoing improvement. Lastly, the study revealed no correlation between respondents’ demographic profiles and their technology leadership practices.